2007
DOI: 10.1021/jm060834d
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Based Design of Sphingosine 1-phosphate-3 Receptor Antagonists That Include a 3,4-Dialkoxybenzophenone Scaffold

Abstract: Sphingosine 1-phosphate (S1P) receptors are G-protein-coupled receptors. Among the five identified subtypes S1P1-5, the S1P3 receptor expressed on vascular endothelial cells has been shown to play an important role in cell proliferation, migration, and inflammation. A pharmacophore-based database search was used to identify a potent scaffold for an S1P3 receptor antagonist by common feature-based alignment and further validated using the Güner-Henry (GH) scoring method. Assumed excluded volumes were merged int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…Finally, 3a-P is 1 log order more potent than previously reported S1P 3 antagonists. 25 However, we do not know at present whether antagonism at the S1P 3 receptor would have any therapeutic benefit.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, 3a-P is 1 log order more potent than previously reported S1P 3 antagonists. 25 However, we do not know at present whether antagonism at the S1P 3 receptor would have any therapeutic benefit.…”
Section: Discussionmentioning
confidence: 96%
“…The (R)-3-amino-(3-hexylphenylamino)-4-oxobutylphosphonic acid (W146)/3-amino-4-(3-hexylphenylamino)-4-oxobutyl phosphonic acid (W140) chiral pair is very useful; W146 is an S1P 1 antagonist and its enantiomer, W140, is an agonist at the same receptor (GonzalezCabrera et al, 2008). Although still not well studied, it was reported that 2-undecyl-thiazolidine-4-carboxylic acid (CAY10444) is a specific S1P 3 antagonist (Koide et al, 2007). The success of FTY720 in the clinic has spurred the search for similar molecules, particularly with S1P 3 -sparing activity.…”
Section: B Sphingosine 1-phosphate Receptor Compoundsmentioning
confidence: 99%
“…Chinese hamster ovary K1 cells that stably expressed human S1P 1 (S1P 1 -CHO), S1P 2 (S1P 2 -CHO), or S1P 3 (S1P 3 -CHO) receptors were maintained as described previously (Koide et al, 2007). A human recombinant S1P 4 receptor-expressing cell line (S1P 4 -Chem) was purchased from Millipore.…”
Section: Cell Culturementioning
confidence: 99%
“…Human coronary artery smooth muscle cells (HCASMCs) purchased from Kurabo were cultured in HuMedia-SG2. [Ca 2ϩ ] i in S1P 1 -, S1P 2 -, S1P 3 -CHO, and S1P 4 -Chem was measured using the calcium-sensitive dye Fura-2 acetoxymethyl ester, as described previously (Koide et al, 2007). The fluorescence (excitation at 340 and 380 nm, emission at 510 nm) was measured with a FLEXStation II (Molecular Devices, Sunnyvale, CA).…”
Section: Cell Culturementioning
confidence: 99%